US-Mexico economic relations: reality, challenges, and future prospects (International Journal of Financial, Administrative and Economic Sciences, 2025)
This research, entitled “U.S. Mexican Economic Relations: Reality, Challenges, and Future Prospects,” comprises an introduction, three principal sections, and a conclusion. The introduction underscores the distinct nature of U.S. Mexican relations and the significant influence exerted by successive U.S. administrations on Mexico since the establishment of both states, particularly in the economic sphere. Although the two countries share similarities in several political practices, and despite the United States maintaining the world’s largest economy, their bilateral relationship has evolved into one of the most extensive and interconnected economic partnerships across numerous sectors. Nonetheless, these economic relations witnessed heightened tension following the inauguration of President Donald Trump in January 2025.The first section, the theoretical framework, provides a comparative analysis of the United States and Mexico, focusing on historical development, the strategic importance of their geographical locations, and their respective regional and international political roles. Mexico remains among the closest and most vital partners of the United States, sharing a land border exceeding 3,000 km and encompassing 47 active land ports of entry. The two countries possess a rich and intertwined historical legacy spanning more than two centuries of diplomatic relations 1822 to the present, shaping profound political, economic, social, and cultural linkages. These relations directly impact the livelihoods of millions of citizens in areas including trade, economic development, educational cooperation, public security, drug control, migration, human trafficking, entrepreneurship, innovation, environmental protection, climate change, and public health.The second section analyzes the current state of economic relations through updated statistical indicators addressing human and natural resources and the economic capacities of both states, including land area, population, GDP, total financial reserves, foreign investment, and external debt. It further examines bilateral merchandise trade between 2016 and 2024, reaffirming Mexico’s position as one of the United States’ most significant trading partners.The third section addresses key economic disputes, chiefly customs tariffs, widely employed by U.S. administrations as a pressure instrument on Mexico, challenges related to the shared land border, particularly migration from Latin America through Mexico into the United States, and the proposal to rename the Gulf of Mexico as the Gulf of America.
Keywords: United States; Mexico; Trade Exchange; Customs Ttariffs; Migration